2018
DOI: 10.3390/polym10090949
|View full text |Cite
|
Sign up to set email alerts
|

A Hyaluronic Acid Based Injectable Hydrogel Formed via Photo-Crosslinking Reaction and Thermal-Induced Diels-Alder Reaction for Cartilage Tissue Engineering

Abstract: A hyaluronic acid (HA) based injectable hydrogel with gradually increasing mechanical properties was synthesized via photo-crosslinking reaction and thermal-induced Diels-Alder (DA) reaction. The injectable hydrogel can quickly gelate within 30 s by photo-crosslinking of HA-furan under the catalysis of lithium phenyl-2,4,6-trimethylbenzoylphosphinate (LAP). This injectable property is beneficial to keep the encapsulated cell activity and convenient for clinical operation. And the mechanical properties can be c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 44 publications
1
31
0
Order By: Relevance
“…Consistent with our results, it can be seen that the tissue engineered cartilage is similar in height and texture to the surrounding normal cartilage after 12 weeks [5]. Some studies have wrapped chondrocytes with hyaluronic acid composite hydrogel, and found that it can maintain the phenotype and high activity of cartilage cells, and increase the expression of cartilage matrix [36].In another study, in vivo experiments for the repair of cartilage defects in rabbits using gelatin-polylactic acid multilayer gel and BMSCs have shown the formation of hyaline cartilage by the fourth week post-implantation [37]. The results of this study showed that the new generated cartilage staining in hydrogel+BMSCs group is close to the surrounding tissue, and chondrocytes can be seen in it.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our results, it can be seen that the tissue engineered cartilage is similar in height and texture to the surrounding normal cartilage after 12 weeks [5]. Some studies have wrapped chondrocytes with hyaluronic acid composite hydrogel, and found that it can maintain the phenotype and high activity of cartilage cells, and increase the expression of cartilage matrix [36].In another study, in vivo experiments for the repair of cartilage defects in rabbits using gelatin-polylactic acid multilayer gel and BMSCs have shown the formation of hyaline cartilage by the fourth week post-implantation [37]. The results of this study showed that the new generated cartilage staining in hydrogel+BMSCs group is close to the surrounding tissue, and chondrocytes can be seen in it.…”
Section: Discussionsupporting
confidence: 91%
“…To address these challenges, researchers have focused on the development of novel biomaterials with potential in tissue engineering and regeneration to facilitate bone regeneration [ [10] , [11] , [12] , [13] ]. Among synthetic biomaterials, hydrogels consisting of natural or synthetic polymers that exhibit excellent mechanical properties and biocompatibility are ideal scaffolds to emulate extracellular matrices for cell proliferation and differentiation [ 12 , [14] , [15] , [16] , [17] ], thus leading to broad utilization in bone regeneration. Thus far, many synthetic polymers, including poly (ethylene glycol), poly (vinyl alcohol), poly (acrylic acid), and poly (lactic acid), among others, have been utilized to develop hydrogels [ [18] , [19] , [20] , [21] ].…”
Section: Introductionmentioning
confidence: 99%
“…The injectable hydrogels can be formed by in situ chemical crosslinking or by the sol-gel or fluid-gel transition. In situ chemical crosslinking is a conventional approach to prepare a stable hydrogel [ 14 , 15 , 16 , 17 , 18 , 19 ]. For instance, the free radical chain growth polymerization of activated acrylates [ 16 ], click chemistry of alkynes and azides [ 17 ], and conjugate Michael addition of multifunctional thiol and activated -ene precursors [ 18 , 19 ] could result in stable hydrogels in situ.…”
Section: Introductionmentioning
confidence: 99%